¡Take Your Soup! Communitarian Initiative (Soup for All) as a tool for mobilization towards gas shale exploration in Guasca, Cundinamarca - Bernal Moreno, Helber Mauricio (2019)
This article analyzes the way food is used as an element of social cohesion and mobilization in rejection of the implementation of a shale gas extraction project in the municipality of Guasca, through the technique of fracking. In this case, a local organization called “Mountain Fortitude Community Association” uses the communitarian initiative (soup for all) not only as an element to mitigate hunger, but also as a means of visibility to the various conflicts that may arise from the development of an extractive practice. This way, positions in favor of the protection of food and territory and voices against it can be evidenced. This allows demonstrating that food is closely related to economic, cultural and political aspects of a given context.